2013
DOI: 10.1007/s40565-013-0028-9
|View full text |Cite
|
Sign up to set email alerts
|

Small signal stability analysis of power systems with high penetration of wind power

Abstract: The integration of large amount of wind power into a power system imposes a new challenge for the secure and economic operation of the system. It is necessary to investigate the impacts of wind power generation on the dynamic behavior of the power system concerned. This paper investigates the impacts of large amount of wind power on small signal stability and the corresponding control strategies to mitigate the negative effects. The concepts of different types of wind turbine generators (WTGs) and the principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Equation 15 can be built for each dynamic component, and it constitutes the basic block for analyzing the interactions among the components in a power system. It describes individual component dynamics in the frequency domain.…”
Section: Building Feedback Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation 15 can be built for each dynamic component, and it constitutes the basic block for analyzing the interactions among the components in a power system. It describes individual component dynamics in the frequency domain.…”
Section: Building Feedback Modelmentioning
confidence: 99%
“…It describes individual component dynamics in the frequency domain. Another advantage of building the input-output transfer function model as Equation 15 lies in its amenity in packing any individual dynamic component into a block. Assume the component j and k will be combined forming a new block denoted as JK.…”
Section: Building Feedback Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased penetration of wind energy leads to increased rate of variation of net load demand on the grid with reduced operational stability [1]. Large scale integration of wind energy may lead to increase in interarea oscillations [2]. When these sources are synchronized with thermal power generation stations, there are many issues arising such as increased frequency fluctuations, increased losses and reduced operating efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate energy consumption when the vehicle needs to run on a maglev area, additional technology has also been proposed to implement wind energy into the vehicle while it is in motion as a backup energy source. Thus, a detailed mathematical modeling using Matlab Simulink software has been implemented for this wind energy utilization for the vehicles by performing turbine and drivetrain modeling [ 11 – 13 ]. A concerted research effort has been performed recently on climate science and found that currently 400 ppm CO 2 is present in the atmosphere causing global warming, which required to cut down 300 ppm CO 2 to confirm global cooling at comfortable stage [ 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%